2018
DOI: 10.1007/s12035-018-1275-6
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Brain Redox Homeostasis, Microglia Activation and Neuronal Damage Induced by Intracerebroventricular Administration of S-Adenosylmethionine to Developing Rats

Abstract: S-Adenosylmethionine (AdoMet) concentrations are highly elevated in tissues and biological fluids of patients affected by S-adenosylhomocysteine hydrolase deficiency. This disorder is clinically characterized by severe neurological symptoms, whose pathophysiology is not yet established. Therefore, we investigated the effects of intracerebroventricular administration of AdoMet on redox homeostasis, microglia activation, synaptophysin levels, and TAU phosphorylation in cerebral cortex and striatum of young rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Sudduth et al [ 56 ] linked hHcy also with the vascular cognitive impairment, neuroinflammation, reduced synaptophysin and tau phosphorylation [ 57 ]. Combination of all mentioned events could finally, on the morphological level, affect astrocytes, as we have already described in our previous studies [ 2 , 24 , 25 , 52 ], or microglia and in turn neurons, detected in this study [ 58 ].…”
Section: Discussionsupporting
confidence: 71%
“…Sudduth et al [ 56 ] linked hHcy also with the vascular cognitive impairment, neuroinflammation, reduced synaptophysin and tau phosphorylation [ 57 ]. Combination of all mentioned events could finally, on the morphological level, affect astrocytes, as we have already described in our previous studies [ 2 , 24 , 25 , 52 ], or microglia and in turn neurons, detected in this study [ 58 ].…”
Section: Discussionsupporting
confidence: 71%
“…Extracellular leakage of Tau species from damaged neurons can act as a trigger for microglial activation and migration, which ultimately will be beneficial as a biomarker for early onset and as a target for therapy Iba1 is a calcium-binding protein receptor, which functions as a marker for microglia or brain-infiltrating macrophages in the synaptic surveillance [79,80]. During neuronal injury-mediated inflammation, Iba1 level becomes upregulated in the brain microenvironment, which correlates with the accumulation of migratory microglia and activated serotype into the site of injury [41,63]. On the contrary, we evidenced the increased level and localization of Iba1 proteins towards the microglial actin-containing membrane projection upon the exposure of extracellular protein aggregates, which may suggest that the Ca 2+ -mediated activation and actin-mediated migration of microglia lead to the rapid clearance of deposits [81].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of F-actin-rich structural components at the front of polarized microglia generates tensile force and retracts its rear extensions for forward movement [38]. Upon tissue injury or protein aggregation, the microglia become activated [39] and migrated by the upregulation of cytoskeletal network with the localized accumulation of calcium-binding protein-Iba1, which in turn mediates the phagocytosis of protein deposits in neurodegeneration [40][41][42]. Upon activation, different cytokines determine the expression of matrix metalloproteases, cathepsins, and heparanase for tissue hydrolysis, facilitating chemotactic migration of microglia, which leads to phagocytic clearance of damaged cells, protein deposits, and pathogens [43].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this overwhelming evidence, an earlier cytokine-based conclusion that melatonin may not be an important modulator of macrophage and microglia function [ 60 ] appears to be obsolete. In addition to the many data concerning anti-inflammatory signaling within the microglial regulatory network, various studies have observed the suppression of microglia activation and microgliosis by melatonin under various conditions and often along with attenuated astrocyte activation [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Conversely, microglia activation can be aggravated by pinealectomy [ 71 ].…”
Section: Melatonin Suppresses Proinflammatory and Favors Anti-inflammatory Signalingmentioning
confidence: 99%